WIDOWS IN WAR ZONES FROM THE PEN OF TAHMIMA ANAM, ‘A GOLDEN AGE’ (INTERNATIONAL JOURNAL OF ENGLISH LANGUAGE AND LITERATURE STUDIES (IJELLS), 2023)
In this present paper the contents are mentioned through the “Widow in War Zone in Tahmima Anam‟s A Golden Age” which explores the condition of a widow in the times of war.The conclusion explains that the writers under study have challenged the patriarchal system that is responsible for the oppression of widows. All the works under study represent the voices of exploited and oppressed. The widow narratives under study present day to day experiences of widows, memories of their past and their struggle in present. The research design is descriptive and explorative. The study has its own restrictions with limits of the aspects discussed by the selected authors in their mentioned novels.